2008
DOI: 10.1029/2007jd009529
|View full text |Cite
|
Sign up to set email alerts
|

A five‐year study of coastal recirculation and its effect on air pollutants over the East Mediterranean region

Abstract: [1] Many studies have shown that air pollutants concentrations in coastal cities may be gravely affected by coastal recirculation. In this study an attempt is made to examine the properties of coastal recirculation over a long period (5 yrs) at multiple sites along the East Mediterranean Sea (EMS). For this purpose, a single station quantitative measure of horizontal recirculation is used based on wind field measurements over periods of 1-96 hrs. The horizontal recirculation is examined with respect to the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 50 publications
2
48
0
Order By: Relevance
“…During the rainy months studied here (November-March), EM Sea Surface temperatures are usually warmer than the adjacent land by 2-10 • C, making LB a common phenomena during the winter (Neumann, 1951;Goldreich, 2003;Levy et al, 2008). The LB magnitude varies both diurnally: maximum (minimum) Land-Sea Temperature Difference (LSTD) at sunrise (afternoon), and seasonally: maximum (minimum) LSTD during December (March).…”
Section: Eastern Mediterraneanmentioning
confidence: 99%
See 1 more Smart Citation
“…During the rainy months studied here (November-March), EM Sea Surface temperatures are usually warmer than the adjacent land by 2-10 • C, making LB a common phenomena during the winter (Neumann, 1951;Goldreich, 2003;Levy et al, 2008). The LB magnitude varies both diurnally: maximum (minimum) Land-Sea Temperature Difference (LSTD) at sunrise (afternoon), and seasonally: maximum (minimum) LSTD during December (March).…”
Section: Eastern Mediterraneanmentioning
confidence: 99%
“…1.1). Ground based radar observations near the Israeli coastline show a 1:1 to 3:1 sea to land rainfall ratio during winters (Levin et al, 2004), with the ratio peak in November, suggesting a stronger contribution of LB in the early stages of winter. Further evidence for LB effect is manifested through diurnal variation of lightning activity (Altaratz et al, 2003), showing a clear maximum of flashes number over sea (land) during midnight (afternoon).…”
Section: Eastern Mediterraneanmentioning
confidence: 99%
“…pieces of work showed a good correlation between the recirculation parameter and the pollutant concentrations and confirmed the effectiveness of R. The authors [16] have shown that the integration period of 24 hours is optimal for recirculation assessment, regardless of the start time of integration and weather patterns. Our results are obtained by integrating over 24 hours, starting at 0 hours.…”
Section: Methodsmentioning
confidence: 53%
“…A lot of investigations [6,12,14,16,19,22,30] were devoted to the assessment of such conditions using Rand accompanied by measurements of the concentration of pollutants. These Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation